2018
DOI: 10.2298/tsci170720103b
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic investigation of organic Rankine cycle energy recovery system and recent studies

Abstract: Recently, new environment-friendly energy conversion technologies are required for using energy resources valid to power generation. Accordingly, low-grade heat sources as solar heat, geothermal energy, and waste heat, which have available temperatures ranging between 60 and 200 °C, are supposed as applicants for recent new generation energy resources. As an alternative energy source, such low-grade heat sources usage generating electricity with the help of power turbine cycles was examined through this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This system is similar to the conventional Rankine Cycle, differed by using organic fluids instead of water. Organic fluids have lower critical pressures and lower evaporation temperatures, allowing lower temperature thermal sources [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This system is similar to the conventional Rankine Cycle, differed by using organic fluids instead of water. Organic fluids have lower critical pressures and lower evaporation temperatures, allowing lower temperature thermal sources [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Organic Rankine cycle power generation system has been extensively studied because it can effectively utilize medium and low temperature heat sources. Hasan Koten et al [1] carried out a detailed study of ORC system and a variety of working fluids, and concluded that its power generation efficiency is between 10-20%. As an important part of ORC system, condenser can provide a lower outlet back pressure for steam turbine to improve the power generation of the system.…”
Section: Introductionmentioning
confidence: 99%
“…An example of how to use the waste heat for electricity production is implementation of Organic Rankine Cycle (ORC). This case was numerically studied via thermodynamic modelling of system component in [5]. Analysis has shown that, using a heat source with temperature of 700 C and mass flow rate of 0,23 kg/s, turbine power of ORC system is 5,2 kW, with average turbine efficiency of 50 %.…”
Section: Introductionmentioning
confidence: 99%